Measuring professional satisfaction and nursing workload among nursing staff at a Greek coronary care unit - Gouzou, Maria; Karanikola, Maria; Lemonidou, Chryssoula; Papathanassoglou, Elizabeth; Giannakopoulou, Margarita (My University, 2015)
Objective: To explore potential associations between nursing workload and professionalsatisfaction among nursing personnel (NP) in Greek Coronary Care Units (CCUs).Method: A cross-sectional study was performed involving 66 members of the NPemployed in 6 randomly selected Greek CCUs. Job satisfaction was assessed by theIWS and nursing workload by NAS, CNIS and TISS-28. Results: The response ratewas 77.6%. The reliability of the IWS was α=0.78 and the mean score 10.7 (±2.1, scalerange: 0.5-39.7). The most highly valued component of satisfaction was "Pay", followedby "Task requirements", "Interaction", "Professional status", "Organizational policies" and"Autonomy". NAS, CNIS and TISS-28 were negatively correlated (p≤0.04) with thefollowing work components: "Autonomy", "Professional status", "Interaction" and "Taskrequirements". Night shift work independently predicted the score of IWS. Conclusion:The findings show low levels of job satisfaction, which are related with nursing workloadand influenced by rotating shifts.
Keywords: Coronary care unit; Job satisfaction; Nursing; Professional autonomy; Shift work; Team; Workload